A viscoelastoplastic constitutive model of semi-crystalline polymers under dynamic compressive loading: Application to PE and PA66. Issue 15 (3rd August 2020) - Xu, Lizhi; Du, Zhonghua; Wang, Jiangbo; Cheng, Chun; Du, Chengxin; Gao, Guangfa
Abstract: Two semi-crystalline polymers: polyethylene and polyamide 66 are selected for experiments over a wide range of strain rates (10 −2 –1 s −1 and 1000–4000 s −1 ) at indoor temperature. The Young modulus and yield stress of these two materials show a great strain-rate sensitivity, implying that the semi-crystalline polymers possess obviously viscous properties. Based on the mechanical response of the materials, a corporative viscoelastoplastic constitutive model is developed to describe the dynamic response of semi-crystalline polymers. In the elastic region, a modified Kelvin model is employed to represent the viscoelastic behavior. In the post-yield regime, combining the modified Eyring theory and the strain hardening model, a corporative model is built to characterize the viscoelastic and strain hardening properties. Comparing to the experimental results for compression at high strain rates, it shows that the constitutive model accurately describes the mechanical dynamic response of semi-crystalline polymers.